2018
DOI: 10.1051/matecconf/201817404007
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Polish voivodeships with regards to the accident rate in the construction industry

Abstract: Abstract. The article classifies Polish voivodeships into appropriate groups with a similar level of occupational safety in the construction industry. The basis for the adopted classification was statistical data published by the Central Statistical Office regarding population, employment in the construction industry, the value of construction production and the number of occupational accidents. The conducted research allowed a logical and correct, in terms of content, division of the Polish territory to be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The method of hierarchical cluster analysis, and also the agglomeration technique of grouping and binding objects using the Ward method [17], which results in the dendrogram, is proposed in order to determine the number of clusters. Depending on the location of cutting off the branch of the dendrogram, a variable number of clusters is obtained [18,19,20]. According to [14], the cut-off location can be determined using various methods, including the Mojena rule [21].…”
Section: Fig 1 Scheme Of Research Methodologymentioning
confidence: 99%
“…The method of hierarchical cluster analysis, and also the agglomeration technique of grouping and binding objects using the Ward method [17], which results in the dendrogram, is proposed in order to determine the number of clusters. Depending on the location of cutting off the branch of the dendrogram, a variable number of clusters is obtained [18,19,20]. According to [14], the cut-off location can be determined using various methods, including the Mojena rule [21].…”
Section: Fig 1 Scheme Of Research Methodologymentioning
confidence: 99%
“…Based on the authors' previous research [34,35], it was found that the basic factors that characterize construction activity are: the value of construction production, the potential of construction enterprises, the generic structure of business entities, employment and its volatility, and also occupational safety. Each of the above-mentioned factors is characterized by a number of sub-factors, which describe in detail the examined aspect.…”
Section: Proposed Research Methodologymentioning
confidence: 99%